Real life study of three years omalizumab in patients with difficult-to-control asthma - López Tiro, J Jesús; Contreras, E Angélica Contreras; del Pozo, M Elena Ramírez; Gómez Vera, J; Larenas Linnemann, D (Allergologia et immunopathologia, 2015)
Even though there are multiple options for the treatment of asthma, there still exists a fair group of patients with difficult-to-control asthma. We describe for the first time the real-world effects of three-year omalizumab treatment on patients with difficult-to-control asthma, seen in a social security hospital in a Latin American country. Difficult-to-control asthmatic patients from the out-patient clinic of a regional hospital were recruited to receive a three-year omalizumab course. Efficacy parameters were asthma control test (ACT) score; FEV1; daily beclomethasone maintenance dose; and unplanned visits for asthma exacerbations (emergency room (ER), hospitalisations, intensive care). 52 patients were recruited, 47 completed the three-year treatment (42 female, 15-67 years, mean age 43.5). Comparing efficacy parameters of the year before omalizumab with the 3rd year of omalizumab: mean ACT improved from 12.4 to 20.5, mean FEV1 from 66.3% (standard deviation (SD) 19.1%) to 88.4% (SD 16.2%) of predicted, while mean beclomethasone dose reduced from 1750 to 766 mcg/day and there was a significant reduction in patients experiencing ER visits (from 95% to 19%, p<0.0001), hospitalisation (38% to 2%, p<0.0001) and intensive care (4% to 0, NS). Five patients discontinued omalizumab, two because of an adverse event (anaphylaxis, severe headache, both resolved without sequelae). Omalizumab improved most clinical parameters of Mexican patients with difficult-to-control asthma. Especially the rates of ER visits and hospitalisation were significantly reduced, thus reducing costs. Omalizumab was generally well tolerated.